Assessment of Community Pharmacists Knowledge on dispensing of Antimicrobial drugs and Prevention of Antimicrobial Resistance in Community practice: Pharmaceutical Science-Clinical Pharmacy - Nisar Ahmed; Mohanta GP; Bhagat MP (International Journal of Life Science and Pharma Research, 2022)
The antimicrobial resistance has more impact on the health care division which would increase the mortality and hospital readmission duration. Our objective is to assess the community pharmacist’s knowledge on dispensing of antimicrobial drugs and prevention of antimicrobial resistance in community practice. A cross-sectional study was conducted for six months. A sample size of 150 registered community pharmacists participated in the study. We have used simple random techniques to select the community pharmacists. Questionnaire were distributed to the community pharmacists at pre and post visits and the response was analyzed. The collected data was analyzed using graph pad prism software. The mean and standard deviation was calculated and P<0.005 was considered to be statistically significant. For 25-30 years of age , community pharmacists were more 68 (45.33%) as compared to other ages. Pre visit before and after average mean antimicrobial resistance score was found to be 4.87. Proper implementation of antimicrobial resistance prevention programmes would drastically increases the rational use of antimicrobials could and minimizes the health care cost.